Social and Humanitarian Factor in South Korea's External Relations and The Korean Question - O. S. Pugacheva (Vestnik MGIMO-Universiteta)
The development of the socio-humanitarian dimension of world politics provides new opportunities for enhancing the role and influence of the middle powers in the global affairs. That is why for understanding and assessment of their political opportunities on the international arena, it is necessary to analyze the approaches and policies of such countries on using socio-humanitarian factor to balance in the existing world balance power and ensure their foreign policy interests. The aim of the article is to analyze South Korea’s activities in the social and humanitarian sphere of world politics in the context of its foreign policy interests. The research question is: what is the role of the socio-humanitarian factor, in particular public diplomacy, in the external activities of South Korea with regard to the settlement of the Korean question? The author argues that South Korea sees social and humanitarian sphere as a possibility to strengthen its role and influence on the international arena. While developing the discourse of South Korea as a middle power, the South Korean leadership seeks to take part in creating norms and rules in different fields of global governance. Despite controversies concerning its status and policy as that of a middle power, South Korea advances through public diplomacy the discourse that constructs and enhance its middle power status and can contribute in forming the corresponding national identity. South Korea uses national branding as well to strengthen its political image. Further, the article points out that promoting South Korea’s stance and defending its interests on the Korean Peninsula represent a key task of South Korea’s public diplomacy. In particular, the article examines South Korea’s public diplomacy mechanisms on the Korean track towards the United States and emphasizes that although South Korea has actively engaged in public diplomacy in the USA, it still has a lot to do to explain South Korea's concerns to American political elites and U.S. publics and ensure that the relationship with the United States fully serves South Korean interests. Moreover, it is noted that enhancing South Korea’s role in global governance as well as forming constructive unification discourse (unification as a process now and as a result someday in the future) within the country and abroad are supposed to expand its opportunities to maneuver in the regional politics of East Asia and provide support for the South Korean initiatives on the Korean settlement. In the end, the author turns to the inter-Korean relations. The author states that different South Korean administrations have prioritized different functions of the socio-humanitarian factor. Conservative administrations put an emphasis on information pressure on the DPRK while the development of inter-Korean relations was conditioned by the denuclearization of North Korea. Progressive administrations prefer engaging the DPRK in social, humanitarian and economic interactions. In the first case the result was a rollback in inter-Korean relations with the North Korean leader-ship receiving additional grounds for the development of its military nuclear program. In the second case the social and humanitarian area was and remains a dimension providing promising opportunities for cooperation that is beneficial to the both parties as it is aimed at solving specific and practical problems of common interest. In that sense, the author argues that social and humanitarian factor in inter-Korean relations could serve as a safety cushion during intensification of the inter-Korean conflict and provide a launch pad for finding a way out of the impasses.